Design of studies on neoadjuvant therapy for intrahepatic cholangiocarcinoma - Yuan Cheng; Xiangcheng Li (Heliyon)
The high recurrence rate and dismal prognosis of localized intrahepatic cholangiocarcinoma (ICC) indicate the unmet need for effective adjuvant and neoadjuvant therapy. In recent years, progress has been made in immunotherapy and targeted therapy for the treatment of advanced biliary tract cancer (BTC), leading to clinical exploration of the provision of these therapies in the perioperative period. Based on years of experience in clinical research on hepatobiliary cancers, the authors discuss the design of studies on neoadjuvant therapy for ICC, aiming to provide references for future neoadjuvant studies.